2009
DOI: 10.1590/s1678-77572009000200004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of human and bovine substrate on the microleakage of two adhesive systems

Abstract: The aim of this study was to evaluate in vitro the marginal sealing of two adhesive systems and to analyze the influence of human and bovine substrates on marginal microleakage in enamel. Rectangular-shaped class V cavities (4 mm wide × 2 mm high × 2 mm deep) were made as follows: 8 cavities were prepared on the buccal and lingual surfaces of the human teeth with margins located on enamel and 16 cavities were prepared on the buccal surfaces of the bovine teeth. The cavities were randomly assigned to 4 groups o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…Bovine enamel has been used in numerous studies investigating adhesion of dental adhesives [36][37][38] and sealing properties of surface sealants 31,39,40 . A resent study by Almeida et al (2009) showed no significant difference between human and bovine substrates concerning microleakage of adhesively fixed restorations in enamel 41 .…”
Section: Discussionmentioning
confidence: 93%
“…Bovine enamel has been used in numerous studies investigating adhesion of dental adhesives [36][37][38] and sealing properties of surface sealants 31,39,40 . A resent study by Almeida et al (2009) showed no significant difference between human and bovine substrates concerning microleakage of adhesively fixed restorations in enamel 41 .…”
Section: Discussionmentioning
confidence: 93%
“…Three of the seven studies found that microleakage values were higher in bovine compared to human substrates, both in enamel (7) and dentin (78,82). On the other hand, three studies found no significant differences in marginal microleakage between human and bovine teeth, both in enamel (83)(84)(85) and dentin (83,84). Camargo et al (86) showed that the penetration of 38% hydrogen peroxide bleaching agent into pulp chambers was higher in human teeth compared to bovine teeth, regardless of the restorative material used.…”
Section: Dental Erosion/abrasion Studiesmentioning
confidence: 97%
“…Inconsistent recommendations were proposed regarding the use of bovine substrate as an alternative to human substrate in bonding/adhesive strength studies. Table 4 illustrates seven in vitro studies reviewed in this category (7,78,(82)(83)(84)(85)(86). Three of the seven studies found that microleakage values were higher in bovine compared to human substrates, both in enamel (7) and dentin (78,82).…”
Section: Dental Erosion/abrasion Studiesmentioning
confidence: 99%
“…Additionally, no significant differences in enamel microleakage have been observed between human and bovine substrates. 24 In order to standardize the adhesion area, enamel surfaces were mechanically flattened. This procedure, however, could potentially influence the shear bond strength because differing bonding behaviors have been reported 25 in ground and unground surfaces.…”
Section: Discussionmentioning
confidence: 99%